Islamic Banks Financial Performance Indicators in Dual Banking System: The Case of Indonesia - Junaidi Junaidi; Altri Wahida; Harmita Sari; Suhardi M Anwar (P4M STIE Putra Bangsa, 2021)
The aim of this research is to elaborate the financial performance of Indonesia Islamic banks (IIB). Used factor analysis to examine financial ratios ten Indonesia Islamic banks (IIB) over the period 2010-2019. The result of recent study proven six factors are key point to describe that the majority of financial ratios in this study namely liquidity, capital adequacy, profitability, efficiency, coverage and control are the factors according to the rank. The study also proven that stability of factors and loadings are stable over time. This study provides an indicator performance of IIB and may be worthwhile to stakeholders have interested with Islamic banking. This research has proved the IIB performance towards important aspect of dual banking system such as Indonesia.